Public Transportation Development in Surakarta City in Partnership Governance Perspective - Kristina Setyowati; Salsabila Almas Nadhifa; Retno Suryawati; Priyanto Susiloadi (Indonesian Association for Public Administration (IAPA), 2021)
Transportation plays an important role in mobility in urban areas. Surakarta City provides Bus Rapid Transit (BRT) transportation system, Batik Solo Trans. This research aims to find out the partnership performed by Surakarta City in public transportation development in partnership governance perspective. Data collection was conducted through interview and documentation. Analysis was conducted using Successful Collaborative Partnership principle from Agarwal, Caiola, and Gibson (2015). The research took place in Surakarta City, particularly in PT. Bengawan Solo Trans, PT. Trans Global Mandiri, Transportation Office, and Technical Executive Unit for Transportation as the organizer of feeder along with Bersama Satu Tujuan Cooperative. The research method used here was qualitative one with descriptive approach. The result of research shows that the principle of Successful Collaborative Partnership is analyzed based on 4 principles: (1) Clear Goals: to improve public service safely, comfortably, and affordably to the public; (2) Clear Roles: Government contributes to formulating policy, funding “buy the service” program, licensing, and providing public transportation infrastructure. The private is the operator responsible fully for public transportation management; (3) Trust: Surakarta City government trusts fully the private to perform cooperation, to provide and to manage Batik Solo Trans and feeder bus service; and (4) Commitment: Government and Private are committed mutually to providing transportation infrastructure, managing, maintaining, and operating public transportation.